Improving the Quality of Religious Learning during the COVID-19 Pandemic through a Reflective Model for Islamic Religious Education Teachers - Ahmadi Ahmadi (Ahlimedia Press, 2022)
This study aims to determine the level of effectiveness of the reflective model in improving the quality of learning during the COVID-19 pandemic. The results of this study provide a technical picture of policy making in education units as well as actions that need to be taken to improve the quality of Islamic Religious Education teachers in primary schools. This research shows that Islamic Religious Education teachers in schools have different views and learning styles in responding to the COVID-19 pandemic. As much as 87% of teachers agree with the Learning From Home (LFH) policy, but the rest think that learning will not be of good quality if it is done online. The interesting thing that was revealed in this study was that the teachers of Islamic Religious Education had optimism and enthusiasm to improve the quality of learning through various learning innovations in the midst of a pandemic. Revlective Model emphasizes learning that involves reflective thinking activities in the process. This study used an action research method involving 32 Islamic Religious Education teachers from 30 elementary schools in Mojokerto district. The process of planning, implementing, observing and evaluating is carried out with 2 models, namely synchronous and asynchronous.